Energy Privatization as an Act of Constitutional Violation on the Omnibus Law of Electricity Sector - Ariyanti, S; Wijaya, A U; Kusnadi, S A; Taufiqurrahman, Taufiqurrahman; Bayuaji, R (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The Constitutional Court had classified electric power as a branch of vital product for the country since it influenced and controlled the lives of many people. As a consequence, the management of electric power should be controlled by the state. So, the vital sector of electricity always is the objective of the Privatization concept which eventually affects the loss of state control towards electric power. Moreover, the Government had a plan to create a geothermal holding company, which consisted of Pertamina Geothermal, PLN, and Geodipa. The Electricity Law which had been issued was focused on two things, which were unbundling and privatization. Law No. 20 the Year 2002 and Law No. 30 the Year 2009 had been sued for judicial review process as they were thought to be in contradiction to the 1945 Constitution article 33 paragraphs 2 and 3.  After conducting a judicial review of those Laws and were declared partially/conditionally granted, especially unbundling articles and privatization articles by the Constitutional Court. What became the concern was if the private company entered the state company’s shares, and it was only a matter of time until the state company’s shares decrease and the private company’s shares increase in equity participation way. If this thing happened, a serious violation of the constitution occurred as mandated in the 1945 Constitution article 33 paragraphs 2 and 3.